2014
DOI: 10.1186/1471-2164-15-573
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genomes of sixteen ardeid birds revealing the evolutionary process of the gene rearrangements

Abstract: BackgroundThe animal mitochondrial genome is generally considered to be under selection for both compactness and gene order conservation. As more mitochondrial genomes are sequenced, mitochondrial duplications and gene rearrangements have been frequently identified among diverse animal groups. Although several mechanisms of gene rearrangement have been proposed thus far, more observational evidence from major taxa is needed to validate specific mechanisms. In the current study, the complete mitochondrial DNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 50 publications
(90 reference statements)
6
64
0
Order By: Relevance
“…In each cluster, sequences isolated from different species were intermingled rather than clustered by species, suggesting that trans-species evolution might exist in ardeid birds (Klein 1987;Li et al 2011b). In addition, the closer relationship between non-classical Egeu-DAB4 gene and other nine ardeid DAB2 genes suggested that they might have arisen from a common ancestral gene with a recent gene duplication event, which further implied that non-classical genes might also exist in these nine ardeid birds (Li et al 2011b;Zhou et al 2014). In future studies, it will be necessary to examine whether low population size of the vulnerable Chinese egret could result in inbreeding and genetic drift and then affect the observed polymorphism and allele spectra at MHC loci (e.g., in addition to mutation and selection), to investigate if orthologous non-classical MHC class II genes exist in other ardeid and ciconiiform birds and to consider the potential implications for the MHC class II alpha-chain genes (e.g., DRA) that must partner with divergent betachains.…”
Section: Discussionmentioning
confidence: 97%
“…In each cluster, sequences isolated from different species were intermingled rather than clustered by species, suggesting that trans-species evolution might exist in ardeid birds (Klein 1987;Li et al 2011b). In addition, the closer relationship between non-classical Egeu-DAB4 gene and other nine ardeid DAB2 genes suggested that they might have arisen from a common ancestral gene with a recent gene duplication event, which further implied that non-classical genes might also exist in these nine ardeid birds (Li et al 2011b;Zhou et al 2014). In future studies, it will be necessary to examine whether low population size of the vulnerable Chinese egret could result in inbreeding and genetic drift and then affect the observed polymorphism and allele spectra at MHC loci (e.g., in addition to mutation and selection), to investigate if orthologous non-classical MHC class II genes exist in other ardeid and ciconiiform birds and to consider the potential implications for the MHC class II alpha-chain genes (e.g., DRA) that must partner with divergent betachains.…”
Section: Discussionmentioning
confidence: 97%
“…In spite of this high rate of sequence evolution, the vertebrate mitochondrial genome was long thought to be relatively stable in terms of genome structure, and rearrangements in gene order were thought to be rare events (Boore, 1999; Gissi et al, 2008). However, over the past 15 years, sequence-based studies have revealed that rearrangements are not uncommon, particularly in birds, where several different lineages have undergone repeated rearrangements (Abbott et al, 2005; Bensch and Härlid, 2000; Cho et al, 2009; Eberhard et al, 2001; Gibb et al, 2007; Haring et al, 2001; Mindell et al, 1998a; Morris-Pocock et al, 2010; Roques et al, 2004; Schirtzinger et al, 2012; Singh et al, 2008; Slack et al, 2007; Verkuil et al, 2010; Zhou et al, 2014). Despite the growing list of avian taxa in which changes in mitochondrial gene order have been described, questions persist regarding the mechanisms by which rearrangements occur, the degree to which duplications are retained over evolutionary time, and the effect that these rearrangements have on the function, replication, and evolution of the mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%
“…Gibb et al (2007) reviewed the gene orders found in avian mitochondrial genomes and concluded that there are at least four distinct gene orders within birds, with the typical (chicken) gene order being the ancestral one. Since then, another gene order variant has been found in ruffs (Verkuil et al, 2010), and a recent study that examined mitochondrial genome sequences of 16 ardeid birds found four distinct gene orders, including two that had not been previously described, all thought to be derived from a single ancestral genome rearrangement (Zhou et al, 2014). In all cases known to date, the novel avian gene orders can be derived from a tandem duplication of the control region and neighboring genes followed by subsequent degeneration and/or loss of some of the duplicate genes (Bensch and Härlid, 2000)(see Figure 1 and Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Duplications within mitochondrial genomes are not uncommon, and changes to mitochondrial gene order are widely thought to arise as a result of a sequence 'duplication and deletion' mechanism 14,30,31 . A number of mitochondrial genomes with duplicated sequences have been reported in species with a divergent mitochondrial gene order [31][32][33] . Given the highly unusual gene order of the I. pulchra mitochondrial genome, a genomic duplication such as this could provide evidence for a genomic 'duplication and deletion' rearrangement of genes.…”
Section: Genomic Sequencesmentioning
confidence: 99%